Significance of Platelets and its Indices in Patients with Dengue Fever - Salma Zeb, Owais Qaisar, Nazish Babar, Ayesha Sardar, Muhammad Bilal, Syed Luqman Shuaib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue is a viral infection affecting different parts of the world, particularly the under developed countries including Pakistan. Changes in hematological parameters are frequently observed in dengue viral infection out of which the changes in the structure of platelets and their levels are a predominant factor in dengue viral infection. In view of the foresaid, this study was conducted to find the platelet levels and indices in confirmed cases suffering from dengue fever. Methods: This descriptive cross-sectional study was conducted in Peshawar in a duration of five months from September to December 2022. A total of five hundred patients were screened for dengue viral infection. Blood samples were collected from all suspected dengue infected patients and processed for complete blood count (CBC). Percentage and mean standard deviation were calculated and data were expressed in tables and graphs. Results: Among total suspected patients, one hundred fifty patients were found positive in which highest number of patients were male (65.3%) than female patients (34.7%). The minimum hemoglobin, white blood cells, and platelets were 6.9 g/dl, 2400 g/dl, and 43000 g/dl respectively. Low level of hemoglobin was found in 9.4% patients, 25.3% patients had below normal white blood cell count, and 30.4% patients were observed with less than normal platelet count. Few patients were noted with lower mean platelets volume and plateletcrit than normal. Conclusion: The study showed a significant impact of dengue viral infection on complete blood count. The hemoglobin, WBC, platelets, and platelet indices were potentially affected with dengue viral infection. It is necessary to design a strategy for early diagnosis of dengue infected patients for timely treatment, which can together save patients from severe impact of dengue viral infection such as dengue shock syndrome which could be fatal. Keywords: Dengue viral infection, Hematological parameters, Platelets, Mean Platelets Volume, Plateletcrit, Platelet distributive width.